Mutual Interference of Frequency Hopping with Collision Avoidance Systems - Pust, Radim; Burda, Karel (Společnost pro radioelektronické inženýrství, 2012)
The aim of this article is to quantify and analyze mutual interference of Frequency Hopping with Collision Avoidance (FH/CA) systems. The FH/CA system is a frequency hopping system where stations select the least jammed channel from several possible before the next jump. The article describes a mathematical model that allows determining the upper limit of the probability of collision of multiple FH/CA systems operated in a common band. The dependence obtained for mutual interference of FH/CA systems is compared with the dependence for mutual interference of conventional FH systems. The result of the comparison is a conclusion that, in terms of mutual interference, it is more advantageous to operate the FH/CA systems than the conventional FH systems.
Keywords: frequency hopping; frequency hopping with collision avoidance; dynamic jammer; FH; FH/CA